COMPARISON OF NON-INVASIVE TECHNIQUES FOR AORTIC PRESSURE APPRAISAL AGAINST INVASIVE PRESSURE MEASURES. (June 2018) - Guala, A.; Tosello, F.; Leone, D.; Sabia, L.; D'Ascenzo, F.; Crea, T.; Moretti, C.; Gaita, F.; Veglio, F.; Ridolfi, L.; Milan, A.
Abstract : Objective: In term of prognostic value, aortic blood pressure may be superior compared to the brachial pressure. A non-invasive technique for the computation of aortic pressure from peripheral information through the use of the generalized transfer function (GTF) is the most-used in clinical research. However, the dispersed and biased appraisal of aortic pressure obtained through this technique might hamper the scientific results obtained in population studies. Low-order, patient-specific whole-body mathematical models might help to bridge brachial to aortic pressure waveforms. The object of the present investigation was to compare (i) GTF method, (ii) a patient-specific 1D-0D mathematical model, and (iii) brachial blood pressure in the appraisal of aortic pressure measured through catheter. Figure. No caption available. Design and method: One-hundred patients referred to diagnostic coronary angiography were included. Brachial pressure and tonometric radial waveform were quantified simultaneously to invasive aortic pressure, which was quantified with a calibrated, fluid-filled catheter. End-systolic and end-diastolic left ventricular volumes and carotid-femoral pulse wave velocity were measured immediately prior to the invasive procedure and were used to set the mathematical model. Results: Systolic aortic pressure was underestimated (9.4 ± 11 mmHg, R2 = 0.71) while diastolic aortic pressure was overestimated (4.5 ± 10.2 mmHg, R2 = 0.4) by the GTF method. Mathematical model underestimated systolic (4 ± 16.5 mmHg, R2 = 0.47) and diastolic (3.9 ± 10.4 mmHg, R2 = 0.62) aortic pressure values. Oscillometric brachial pressure overestimated systolic (2.4 ± 12.6 mmHg, R2 = 0.71) and diastolic (3.7 ± 9.8 mmHg, R2 = 0.48) aortic pressure. Both brachial pressure and GTF methods presented a trend for higher systolic and diastolic pressure overestimation for higher aortic pressure, while mathematical modeling did not. Conclusions: Despite oscillometric brachial pressures overestimate aortic pressure extremes its predictions correlate with invasive pressure similarly to both the widely-used GTF method and the subject specific, multiscale mathematical model.